Betulinic acid and obesity-related disorders - Azevedo, Lara; Ferraz, Ricardo; Vieira, Mónica; Prudêncio, Cristina; Fernandes, Sílvia (Frontiers in Pharmacology, 2025)
The obesity epidemic is not just a health issue, it is increasingly driving a shift in the prevalence of chronic diseases, affecting 890 million adults and straining healthcare systems worldwide. Conditions such as type 2 diabetes mellitus, cardiovascular diseases, non-alcoholic fatty liver disease, and various cancer types are closely tied to this growing crisis. Betulinic acid has anti-inflammatory, antioxidant and anti-cancer properties and modulates key metabolic pathways such as NF-κB and AMPK signaling. This compound improves insulin sensitivity, reduces hepatic steatosis, mitigates the progression of atherosclerosis and fibrosis, and suppresses inflammatory responses, which are important in treating those obesity-related disorders. Additionally, betulinic acid use in cancer treatment has been explored due to its potential in angiogenesis and metastasis inhibition and promotion of apoptosis. This review spotlights the therapeutic potential of the natural compound betulinic acid in processes such as insulin sensitivity, glucose and lipid metabolism, adiposity, inflammation, oxidative stress, intestinal microbiota, and other mechanisms underlying different obesity-related disorders. Overall, besides strong therapeutic potential of betulinic acid, described limitations such as poor aqueous solubility, limited bioavailability, production and extraction have resulted in scarce clinical data making it premature to draw definitive conclusions regarding its application in clinical practice.